2017
DOI: 10.1002/adv.21873
|View full text |Cite
|
Sign up to set email alerts
|

A computer model for starve‐fed single‐screw extrusion of polymer blends

Abstract: A new computer model has been developed to simulate a starve-fed single-screw extrusion process of polymer blends. This is a composite model, which is based on combining melt conveying models with new fusion models for polymer blends. The model is able to predict pressure and temperature profiles, filling of the screw and rate of polyblend fusion. Computer calculations were executed for extrusion of highdensity polyethylene and polystyrene blend at various technological conditions, and fill factor, pressure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
0
17
0
3
Order By: Relevance
“…Wilczyński et al based on the polymer melting studies [59,127] developed the first, and, up to now, the only available computer model of this process SSEM-Starve [128]. This model was later extended to non-conventional screw configurations [205,206], and to the extrusion of polymer blends [233,234]. Recently, the global model GSEM (Global Screw Extrusion Model) was developed, which allows the modeling of single screw extrusion both in the flood fed and starve fed mode [205].…”
Section: Computer Models Of Extrusionmentioning
confidence: 99%
“…Wilczyński et al based on the polymer melting studies [59,127] developed the first, and, up to now, the only available computer model of this process SSEM-Starve [128]. This model was later extended to non-conventional screw configurations [205,206], and to the extrusion of polymer blends [233,234]. Recently, the global model GSEM (Global Screw Extrusion Model) was developed, which allows the modeling of single screw extrusion both in the flood fed and starve fed mode [205].…”
Section: Computer Models Of Extrusionmentioning
confidence: 99%
“…According to this model, two stages of melting are distinguished: melting by conduction in the partially filled region of the screw where the polymer granules are collected at the active screw flight and melting by energy dissipation in the fully filled region where the unmolten solid particles are suspended in the previously molten material ( Figure 1b). This basic model was later extended to non-conventional screw configurations [31,32] and extrusion of polymer blends and composites [56][57][58][59].…”
Section: Flood Fed Vs Starve Fed Extrusionmentioning
confidence: 99%
“…Optimization was carried out for single screw extrusion of polyblend composed of high-density polyethylene (HDPE, 85%) and polystyrene (PS, 15%). This immiscible blend [66] was the subject of our recent extrusion studies both experimental and modeling [57,59].…”
Section: Research Programmentioning
confidence: 99%
“…Wilczyński et al [22,23] reported that polymer blends are widely used in industry, but that their melting behavior is substantially different to that of pure polymers. This finding is also confirmed by Cunha et al [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that the plastication of PS was delayed to a much greater distance along the screw compared to the pure material. Tyagi, Domingues, Lindt, Wilczyński et al [22,23,[27][28][29][30][31][32][33][34] published papers dealing with the morphology development of polymer blends in single screw extruders. They pointed out, that the compatibility of the polymers (surface tension, thermodynamically behavior, and the viscosity ratio) and the deformation (shear, elongation) are important parameters for the development of the morphology.…”
Section: Introductionmentioning
confidence: 99%